2021
DOI: 10.1108/sajbs-06-2020-0199
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis among foreign direct investment, trade openness and economic growth: evidence from the Indian economy

Abstract: PurposeThis study examines the long-term and causal relationship among foreign direct investment (FDI) inflows, trade openness and economic growth from India.Design/methodology/approachThis study has used annual time series data from the period 1985–2018 and applied the Johansen cointegration and vector autoregression (VAR) model.FindingsThe results of Johansen's cointegration confirm no long-term relationship among all the above three variables. Further, the results of VAR Granger causality indicate that FDI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 81 publications
3
20
2
Order By: Relevance
“…International trade increases opportunities to invest in domestic countries encourage efficient distribution of resources, and increases productivity. Most significantly trade openness promotes technological expansion and spreads knowledge across economies (Adeleye et al, 2021;Fetahi-Vehapi et al, 2015;Kumari and Sharma, 2017;Kumari et al, 2021). Thus, we expect a positive relationship between TO and EG.…”
Section: Trade Openness (To)mentioning
confidence: 83%
“…International trade increases opportunities to invest in domestic countries encourage efficient distribution of resources, and increases productivity. Most significantly trade openness promotes technological expansion and spreads knowledge across economies (Adeleye et al, 2021;Fetahi-Vehapi et al, 2015;Kumari and Sharma, 2017;Kumari et al, 2021). Thus, we expect a positive relationship between TO and EG.…”
Section: Trade Openness (To)mentioning
confidence: 83%
“…, 2021). Kumari et al. (2021) found that there was a long term causal connection between FDI, trade openness and economic growth in India and FDI and trade openness influenced both ways.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Impact of trade openness on environmental quality Trade openness has a connection and will influence FDI (Burange et al, 2019;Djulius, 2017;Makoni, 2018;Rakshit, 2022;Rathnayaka Mudiyanselage et al, 2021). Kumari et al (2021) found that there was a long term causal connection between FDI, trade openness and economic growth in India and FDI and trade openness influenced both ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The “compensation hypothesis,” related to trade openness, states that government spending is higher in open economies to mitigate against the jeopardy of being exposed to global markets and economic shocks. Some studies conducted in the Indian context to empirically examine the impact of trade openness have also yielded mixed results (Benarroch & Pandey, 2008, 2012; Chatterji, Mohan, & Dastidar, 2014; Dixit, 2014; Hye & Lau, 2014; Jani, Joshi, & Mehta, 2019; Joshi, Jani, & Mehta, 2022; Karras, 2003; Kumari et al. , 2021; Mallick, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%